Temporal frequency of knockdown resistance mutations, F1534C and V1016G, in Aedes aegypti in Chiang Mai city, Thailand and the impact of the mutations on the efficiency of thermal fogging spray with pyrethroids - Plernsub S. (2017)
© 2016 Elsevier B.V. In Thailand, control of dengue outbreaks is currently attained by the use of space sprays, particularly thermal fogging using pyrethroids, with the aim of killing infected Aedes mosquito vectors in epidemic areas. However, the principal dengue vector, Aedes aegypti, is resistant to pyrethroids conferred mainly by mutations in the voltage-gated sodium channel gene, F1534C and V1016G, termed knockdown resistance (kdr). The objectives of this study were to determine the temporal frequencies of F1534C and V1016G in Ae. aegypti populations in relation to pyrethroid resistance in Chiang Mai city, and to evaluate the impact of the mutations on the efficacy of thermal fogging with the pyrethroid deltamethrin. Larvae and pupae were collected from several areas around Chiang Mai city during 2011–2015 and reared to adulthood for bioassays for deltamethrin susceptibility. These revealed no trend of increasing deltamethrin resistance during the study period (mortality 58.0-69.5%, average 62.8%). This corresponded to no overall change in the frequencies of the C1534 allele (0.55–0.66, average 0.62) and G1016 allele (0.34–0.45, average 0.38), determined using allele specific amplification. Only three genotypes of kdr mutations were detected: C1534 homozygous (VV/CC); G1016/C1534 double heterozygous (VG/FC); and G1016 homozygous (GG/FF) indicating that the F1534C and V1016G mutations occurred on separate haplotypic backgrounds and a lack of recombination between them to date. The F1 progeny females were used to evaluate the efficacy of thermal fogging spray with Damthrin-SP ® (deltamethrin + S-bioallethrin + piperonyl butoxide) using a caged mosquito bioassay. The thermal fogging spray killed 100% and 61.3% of caged mosquito bioassay placed indoors and outdoors, respectively. The outdoor spray had greater killing effect on C1534 homozygous and had partially effect on double heterozygous mosquitoes, but did not kill any G1016 homozygous mutants living outdoors. As this selection pressure would be expected to have led to an increase in frequency of the G1016 allele, it is likely that the relatively stable kdr mutation allele frequencies observed here result from balancing selection, in the form of overdominance for VG/FC genotypes and/or the effects of fluctuating environments that vary in insecticide exposure.